Diabetic ketoacidosis fluid management in children: systematic review and meta-analyses. Issue 11 (23rd June 2022) - Hamud, Ali Abdalla; Mudawi, Khalid; Shamekh, Ahmed; Kadri, Ayodeji; Powell, Colin; Abdelgadir, Ibtihal
Abstract : Importance: Diabetic ketoacidosis (DKA) is a serious complication of type 1 diabetes mellitus, which may lead to significant morbidity and mortality. Objectives: To compare the safety and efficacy of liberalised versus conservative intravenous fluid regimens in the management of DKA in children. Data source and study selection: Databases from inception to January 2022: MEDLINE, EMBASE, CINAHL and the Cochrane Central Register of Controlled Trials were included. Only randomised controlled trials (RCTs) that included children aged under 18 years were assessed. Two reviewers performed data assessment and extraction. Data extraction and synthesis: Three studies out of 1536 citations were included. Main outcomes: The time to the recovery from the DKA; the frequency of paeditric intensive care unit (PICU) admissions; development of brain oedema; reduction in Glasgow Coma Scale (GCS); development of acute kidney injury and all-cause mortality. Results: We included three RCTs (n=1457). No evidence of difference was noted in the GCS reduction (risk ratio (RR)=0.77, 95% CI 0.44 to 1.36) or development of brain oedema (RR=0.50, 95% CI 0.15 to 1.68). The time to recovery from DKA was longer in the conservative group (mean difference=1.42, 95% CI 0.28 to 2.56). Time to hospital discharge, adverse or serious adverse events were comparable in the two studied groups. Conclusion: There is no evidence from this meta-analysis that rate of fluid administration has any effect on adverse neurological and other outcomes or length of hospital stay. Abstract : This review and metanalysis of fluid management in paediatric diabetic ketoacidosis found no evidence that the rate of fluid administration has any effect on clinical outcomes or length of stay.